Parenting with disabilities: Experiences from implementing a parenting support programme in Sweden. (June 2013) - Starke, Mikaela; Wade, Catherine; Feldman, Maurice A; Mildon, Robyn
This article reports on the initial stages of implementing an Australian-based education programme for parents with intellectual disabilities (IDs) in Sweden. The clinical utility of the programme, Parenting Young Children (PYC), in the new country context is explored through Swedish professionals' experiences in learning and using it. Study participants found PYC well suited for use in their working environment. Most of them reported the programme to have strengthened their work with parents. The programme was seen as benefiting both the study participants in their work with parents with IDs and these parents themselves, and its structure and content were found to be helpful in several ways. The checklists forming part of PYC were considered useful, but their purpose was sometimes misunderstood. The reported study helps to identify what is needed to improve the translation of the programme into the new country context, to promote appropriate and more effective use of programme materials.